Conversion of Fructose to 5-Hydroxymethyl Furfural: Mathematical Solution with Experimental Validation - Muhammad Sajid; Apu Chowdhury; Ghulam Bary; Yin Guoliang; Riaz Ahmad; Ilyas Khan; Waqar Ahmed; Muhammad Farooq Saleem Khan; Aisha M. Alqahtani; Md. Nur Alam (Journal of Mathematics)
Conversion of fructose to furan aldehydes is a rapidly developing concept considering the emergent scenario of the replacement of fossil-derived components to biomass-derived green precursors. 5-hydroxymethyl furfural (HMF) and levulinic acid (LA) are the two most important bio-precursors with expanded downstream utilization in modern industries. Their production from biomass-derived sugars is a complex reaction due to competitive side reactions with a variety of byproducts. Therefore, their simulated optimization is an important tool that can help for process optimization in an economical way. In this article, we have developed a mathematical solution for fructose conversion, HMF production, and levulinic acid (LA) formation in a reactive environment. The accuracy of the developed model is further verified through experiments and found satisfactory with high accuracy. Therefore, the developed model can be used to simulate the reaction environment and product optimization under a given set of conditions.